The Judas coin - Simonson, Walter (DC Comics, 2012)
"This centuries-spanning original graphic novel from legendary writer/artist Walter Simonson cleverly ties the Biblical story of Judas to the DC Universe. Simonson shows how one of the silver coins Judas was paid to betray Jesus has had an impact on the DC Universe, with chapters starring The Golden Gladiator (70 A.D.), The Viking Prince (900 A.D.), Captain Fear (1740) and Bat Lash (1880). The centerpiece of the book is an epic battle between Batman and Two-Face. The story blasts into the future as well, with a final chapter set in the year 2070." --Amazon.com.